The Phenomenon of Corruption and Efforts to Combat Corruption in Indonesia - La Ode Faiki (PT FORMOSA CENDEKIA GLOBAL, 2023)
Corruption that occurs in Indonesia is very worrying and has an extraordinary negative impact on almost all aspects of life. Corruption has destroyed the economic system, democratic system, political system, legal system, government system, and social order in this country. On the other hand, efforts to eradicate corruption that have been carried out so far have not shown optimal results. Corruption at various levels still occurs as if it has become a part of life and is even considered a normal thing. If this condition is allowed to continue, sooner or later corruption will destroy this country. Corruption has three phenomena which include: bribery, extortion, and nepotism. Corruption usually involves other parties, which contains fraud on public bodies or the general public, betrayal of trust, for self-interest, other people or entities that can harm the country's finances or the country's economy. The formulation classified as a criminal act of corruption today can be seen in Law Number. 31 of 1999 concerning the Eradication of Corruption; juncto (jo) Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes (UUPTPK). The birth of reform has determined corruption as the